OPTIMASI VOLUME NaOH PADA PROSES DELIGNIFIKASI AMPAS TEBU UNTUK PRODUKSI BIOKOAGULAN DAN APLIKASINYA DALAM PENGOLAHAN LIMBAH CAIR POME: Biokoagulan - Putri, Nur Aulia; Ayu Setyowati, Sekar; Tyas Suciningrum, Alfidah; Kurniawan, Andri; Adhiksana, Arief (UIR Press, 2026)
Sugarcane waste (bagasse) is an industrial waste that has a harmful impact on public health because it contains emissions of hazardous combustion products such as volatile organic carbon (VOC) and carbon monoxide (CO). This study aims to utilize bagasse waste as a biocoagulant material in reducing these parameters through the maceration method with an extraction time of 24 hours and varying the volume of solvent (8% NaOH) 50 ml, 100 ml, 150 ml, 200 ml and 250 ml. Bagasse is processed into fine powder and used as an absorbent medium mixed with POME. The results showed that bagasse is effective in reducing TSS, TDS, and turbidity but experienced an increase in pH in POME. The largest decrease occurred in the variation of solvent volume of 250 ml with the maceration method, resulting in a decrease in TSS of up to 99%, TDS of up to 99%, a decrease in turbidity of up to 98% and pH becoming alkaline. These findings indicate that sugarcane bagasse waste has the potential as a cheap and environmentally friendly alternative material in the processing of palm oil liquid waste